Prediction of Storm Surges in the East Coast of Peninsular Malaysia in Response to Climate Change - Rosli, Nurdiyana Nabilah; Hee-Min Teh; Soo-Youl Kim (International Journal of Integrated Engineering, 2024)
This study employed the MIKE 21HD modeling framework, integrating data from the future climate database, "Policy Decision Making for Future Climate Change (d4PDF)" on selected critical ensembles to investigate the impact of climate change on storm surge height (SSH) along the East Coast of Peninsular Malaysia during the Northeast Monsoon season. Three scenarios, including past-historical data, future climate with a 2°C increment (+2K), and future climate with a 4°C increment (+4K), were analyzed. The study had validated model accuracy through root mean square error (RMSE), demonstrating alignment with observed data. Results indicated a correlation between temperature increase and storm surge height (SSH), with higher temperature scenarios leading to more severe surge outcomes. The analysis identified the Future +4K scenarios as yielding the most critical SSH across all stations, with recorded SSH at Kuala Pahang (SSHmax = 1.379 m), Chendering (SSHmax = 1.344 m), Geting (SSHmax = 1.251 m), and Tanjung Sedili (SSHmax = 1.251 m) stations. Considering the findings, it was recommended to reassess the baseline provision for coastal engineering projects, suggesting a storm surge resilience design exceeding the observed maximum. The utilization of d4PDF data in this study laid the groundwork for targeted strategies to mitigate the impacts of climate-induced storm surges in vulnerable coastal regions.